A dual stream hierarchical transformer for starvation grading of golden pomfret in marine aquaculture - Zheng, Kaijian; Yang, Renyou; Li, Rifu; Yang, Liang; Qin, Hao; Li, Ziyun (Frontiers in Marine Science, 2022)
Introduction Fish starvation grading can provide feeding information for aquaculture, reducing the cost of lures and helping to promote the unmanned and intelligent process of offshore aquaculture. Methods In this study, we used golden pompano as the experimental object to address the fish starvation grading problem in the marine culture vessel environment, and proposed the dual stream hierarchical transformer to provide additional temporal information for the starvation grading task, which improved the grading accuracy. We first built a dual stream dataset with both spatial and temporal channel, and divided the fish school starvation status into five levels (very bloated, a little bloated, modest, a little starving, very starving) according to the feeding time and experience. Based on the marine image characteristics, we proposed a dual stream hierarchical transformer with hierarchical convolutional network, composite fusion convolution and transformer. Results and discussion We finally evaluated the efficacy of the model based on qualitative and quantitative analyses, revealing that the proposed dual stream hierarchical transformer achieved the state-of-the-art starvation grading performance with a test accuracy of 98.05%. Our model outperformed other mainstream models, including VGG, ResNet, attentionbased model and other fish status grading related model. Field tests on the vessel further suggested that the model can be applied to the mariculture environment of golden pomfret.